Cross-lingual speech recognition under run-time resource constraints - Yu, Dong; Deng, Li; Liu, Peng; Wu, Jian; Gong, Yifan; Acero, Alex (Proceedings of the ICASSP, 2009)
This paper proposes and compares four cross-lingual and bilingual automatic speech recognition techniques under the constraints of limited memory size and CPU speed. The first three techniques fall into the category of lexicon conversion where each phoneme sequence (PHS) in the foreign language (FL) lexicon is mapped into the native language (NL) phoneme sequence. The first technique determines the PHS mapping through the international phonetic alphabet (IPA) features; The second and third techniques are data-driven. They determine the mapping by converting the PHS into corresponding context-independent and context-dependent hidden Markov models (HMMs) respectively and searching for the NL PHS with the least Kullback-Leibler divergence (KLD) between the HMMs. The fourth technique falls into the category of acoustic-model (AM) merging where the FL’s AM is merged into the NL’s AM by mapping each senone in the FL’s AM to the senone in the NL’s AM with the minimum KLD. We discuss the strengths and limitations of each technique developed, report empirical evaluation results on recognizing English utterances with a Korean recognizer, and demonstrate the high correlation between the average KLD and the word error rate (WER). The results show that the AM merging technique performs the best, achieving 60% relative WER reduction over the IPA-based technique.